Neutrophil-to-Lymphocyte Ratio Predicts the Outcome of Acute Intracerebral Hemorrhage. Issue 6 (June 2016) - Lattanzi, Simona; Cagnetti, Claudia; Provinciali, Leandro; Silvestrini, Mauro
Abstract : Background and Purpose—: Increasing evidence suggests that inflammatory mechanisms are involved in the intracerebral hemorrhage–induced brain injury. We evaluated the prognostic role of the peripheral leukocyte counts and neutrophil-to-lymphocyte ratio (NLR) in patients with intracerebral hemorrhage. Methods—: Patients with acute spontaneous intracerebral hemorrhage were retrospectively identified. Total white blood cells, absolute neutrophil count, and absolute lymphocyte count were obtained and the NLR computed from the admission blood work. The study end point was the occurrence of death or major disability at 3 months. Results—: One hundred seventy-seven subjects were enrolled. Ninety-four (53.1%) had unfavorable outcome. The absolute neutrophil count, absolute lymphocyte count, and NLR were independently associated with the 3-month status. The NLR resulted the best discriminating variable and the best predictive cut-off value was 4.58. Conclusions—: In patients with acute intracerebral hemorrhage, higher neutrophils, lower lymphocytes, and higher NLRs predicted worse 3-month outcome. Abstract : Supplemental Digital Content is available in the text.